Immune Response and Evasion Mechanisms of Plasmodium falciparum Parasites - Esmael Besufikad Belachew (Journal of Immunology Research)
Malaria causes approximately 212 million cases and 429 thousand deaths annually. Plasmodium falciparum is responsible for the vast majority of deaths (99%) than others. The virulence of P. falciparum is mostly associated with immune response-evading ability. It has different mechanisms to evade both Anopheles mosquito and human host immune responses. Immune-evading mechanisms in mosquito depend mainly on the Pfs47 gene that inhibits Janus kinase-mediated activation. Host complement factor also protects human complement immune attack of extracellular gametes in Anopheles mosquito midgut. In the human host, evasion largely results from antigenic variation, polymorphism, and sequestration. They also induce Kupffer cell apoptosis at the preerythrocytic stage and interfere with phagocytic functions of macrophage by hemozoin in the erythrocytic stage. Lack of major histocompatibility complex-I molecule expression on the surface red blood cells also avoids recognition by CD8+ T cells. Complement proteins could allow for the entry of parasite into the red blood cell. Intracellular survival also assists the escape of malarial parasite. Invading, evading, and immune response mechanisms both in malaria vector and human host are critical to design appropriate vaccine. As a result, the receptors and ligands involved in different stages of malaria parasites should be elucidated.